Differential contributions of A- and C-nociceptors to primary and secondary inflammatory hypersensitivity in the rat - Hsieh, Meng-Tzu; Donaldson, Lucy F.; Lumb, Bridget M. (Lippincott, Williams & Wilkins, 2015)
Primary hyperalgesia is characterized by increased responsiveness to both heat and mechanical stimulation in the area of injury. By contrast, secondary hyperalgesia is generally associated with increased responses to mechanical but not heat stimuli. We tested the hypothesis that sensitization in secondary hyperalgesia is dependent on the class of peripheral nociceptor (C- or A-nociceptor) rather than the modality of stimulation (mechanical vs heat). A- and C-nociceptors were selectively activated using contact heat ramps applied to the hind paw dorsum in animals with hind paw inflammation (primary hyperalgesia) and knee inflammatory arthritis (secondary hyperalgesia). Sensitization to A- and C-nociceptor activation in primary and secondary hyperalgesia was assessed by reflex withdrawal thresholds and by Fos immunocytochemistry in the dorsal horn of the spinal cord, as an index of neuronal activation. In primary hyperalgesia, only C-nociceptor-evoked withdrawal reflexes were sensitized. This was associated with increased spinal lamina I neuronal activation to both A- and C-nociceptor activation. Fos-like immunoreactivity (FLI) was unchanged in other dorsal horn laminae. In secondary hyperalgesia, only A-nociceptor-evoked withdrawal reflexes were sensitized, and FLI was increased in both superficial and deep dorsal laminae. Neurons in the superficial dorsal horn receive and process nociceptor inputs from the area of primary hyperalgesia, resulting in functional sensitization to C-nociceptive inputs. In inflammatory arthritis, secondary hyperalgesia is evoked by A-nociceptor thermal stimulation, suggesting that secondary hyperalgesia is A-nociceptor, rather than stimulus modality (mechanical vs thermal), dependent. Fos-like immunoreactivity evoked by A-nociceptor stimulation in secondary hyperalgesia suggests that the sensitization is underpinned by spinal neuronal sensitization in laminae I and IV/V.